Effect of timing of cord clamping (early vs delayed) on hemoglobin level among newborns: an Indian study - S. Jafra, Bikramjit; Mehendiratta, Sunil K.; R. Jafra, Pooja; Jafra, Anudeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of the current study was to evaluate effect of delayed cord clamping on hemoglobin level among newborns and look for any adverse effects following delayed cord clamping. Methods: Total 60 newborns were enrolled in the study and were randomly allocated to either control (early cord clamping 15 secs) and cases (delayed cord clamping 3 mins). Samples were collected in labor room, during birth to check the hemoglobin, billirubin and hematocrit levels in two groups. Follow up data were collected in postnatal ward, 24 hours after birth to estimate hemoglobin, hematocrit and billirubin levels and infants were assessed for the presence of respiratory distress. Results: Hb levels among cases were significantly higher compared to controls at birth. The mean Hb at birth among controls was 14.90±1.28 g/dl and among cases was 16.06±2.37 g/dl (p value 0.023). Hb levels among cases were significantly higher compared to controls at 24 hours. The mean Hb at 24 hours among controls was 16.16±1.70 g/dl and among cases was 19.28±2.16 g/dl (p value <0.001). Conclusions: Hemoglobin and hematocrit levels were significantly increased at birth as well as at 24 hours of age in delayed compared to early clamping group with no significant adverse effects seen in the group with delayed clamping.